Efficacy of Low-Dose Rituximab on Neuromyelitis Optica-Associated Optic Neuritis - Zhao, Shuo; Zhou, Huanfen; Xu, Quangang; Dai, Hong; Wei, Shihui (Frontiers in Neurology, 2021)
Purpose: To prospectively investigate the efficacy and tolerance of low-dose rituximab (RTX) for the treatment of neuromyelitis optica-associated optic neuritis (NMO-ON). Methods: Optic Neuritis patients with seropositive aquaporin 4-antibody (AQP4-Ab) were diagnosed with NMO-ON and recruited for treatment with low-dose RTX (100 mg * 4 infusions) and were then followed monthly for a minimum of 3 months. Reinfusion of 100 mg RTX was given when the CD19+ B lymphocyte frequency was elevated to above 1%. The serum AQP4-Ab level was tested by an enzyme-linked immunosorbent assay (ELISA). Results: A total of 43 NMO-ON patients (1 male/42 female, 75 involved eyes) were included in this study. CD19+ B cell clearance in the peripheral blood was induced in 97.7% of patients after induction treatment. A significant decrease in serum AQP4-Ab concentration was observed after induction treatment (P = 0.0123). The maintenance time of B cell clearance was 5.2 ± 2.25 months. The relapse-free rate was 92.3% in patients followed-up for over 12 months, and patients with non-organ-specific autoimmune antibodies tended to relapse within 6 months. A total of 96.2% of patients had stable or improved vision, and a decrease in the average expanded disability status scale (EDSS) score was found. Structural alterations revealed by optic coherence tomography were observed in both ON and unaffected eyes. The rates of infusion-related reactions and long-term adverse events (AEs) were 18.6 and 23.1%, respectively. No severe AEs was observed. Conclusions: Low-dose rituximab is efficient and well-tolerated in treating NMO-ON.